Trends in and correlates of medical marijuana use among adults in the United States. (1st May 2018) - Han, Beth; Compton, Wilson M.; Blanco, Carlos; Jones, Christopher M.
Highlights: Medical marijuana use among adults increased from 1.2% in 2013 to 1.6% in 2015. The increases were found in both medical and nonmedical marijuana states. Clinicians need to assess evolving patterns of medical marijuana use in patients. Abstract: Background: Trends in and correlates of medical marijuana use are important to inform ongoing clinical, research, policy, and programmatic efforts. This study assessed trends in and correlates of medical marijuana use among U.S. adults. Methods: We analyzed data from approximately 147, 200 U.S. civilians aged 18 or older who participated in the 2013-2015 National Surveys on Drug Use and Health. Descriptive analyses, multivariable logistic regressions, and zero-truncated native binomial regressions were applied. Results: Among U.S. adults, the prevalence of medical marijuana use increased from 1.2% in 2013 to 1.6% in 2015 ( p = 0.0007). After adjusting for covariates, adults residing in medical marijuana states (states with legalized medical marijuana use) were 1.3 times more likely to use marijuana medically in 2015 than in 2013 (adjusted odds ratio (AOR) = 1.3, 95% confidence interval (CI) = 1.03-1.61), and adults in nonmedical marijuana states were 1.4 times more likely to report medical marijuana use in 2015 than in 2013 (AOR = 1.4, 95% CI = 1.05-1.90). Among adults who used marijuana exclusively for medical purposes in the past 12 months, trends in 12-month cannabis use disorders, daily or near daily use, and the number of days of marijuana use remained unchanged during 2013-2015. We identified how correlates of medical marijuana use among adults in medical marijuana states differed from their counterparts in nonmedical marijuana states. Conclusions: Adults were more likely to use marijuana medically in 2015 than in 2013 in both medical and nonmedical marijuana states. Clinicians need to learn about and address evolving patterns of medical marijuana use in patients.